206 ACHIEVING TREATMENT GOALS IN PATIENTS WITH CHRONIC KIDNEY DISEASE. (1st January 2005) - Patel, D.; Mekala, P.; Lenz, O.
Abstract : National guidelines (K/DOQI) have been established for therapeutic goals in patients with chronic kidney disease (CKD). The purpose of this study was to determine whether these treatment goals can be achieved in a dedicated clinic for patients with CKD stages 4 and 5 and to identify predictors for treatment failure. We performed a single center, cross-sectional study of 268 patients scheduled to be seen between 01/01/2004 and 08/31/2004 in the CKD clinic at a large teaching hospital serving mainly minority populations (41% African American, 47% Hispanic). A total of 70 patients were excluded because they had previously started dialysis, did not attend any clinic visit, or had no laboratory data available. Of the remaining 198 patients, 61 had been seen for 6 months or less and fewer than 4 nephrology encounters; these were called "community patients." The remainder had been seen for more than 6 months and had more than 4 nephrology encounters; these were categorized as "CKD clinic patients." The glomerular filtration rate was estimated using the modified Levy formula to classify patients as having CKD stage 4 (GFR 15-29 mL/min/1.73 m2) or stage 5 (GFR < 15 mL/min/1.73 m2). We chose the following outcome measures: serum calcium (corrected for serum albumin), phosphate, calcium-phosphate-product, intact parathyroid hormone, bicarbonate, albumin, and hemoglobin. We defined treatment failure as having less than 4 of these 7 parameters outside the range recommended by K/DOQI guidelines. 32% of all patients met the criteria for treatment failure. Patient characteristics significantly associated with treatment failure were failure to attend clinic visits (no show rate > 25%, odds ratio [OR] 5.1), being a community patient (OR 4.3), need for dialysis (OR 3.3), being younger than 60 years of age (OR 2.6), having CKD Stage 5 (OR 2.5), and being African American (OR 2.3). These parameters with the exception of CKD stage were also significant predictors of treatment failure by logistic regression. In conclusion, achieving K/DOQI treatment goals is a challenging task. Early referral to a dedicated CKD clinic improves the ability to achieve K/DOQI targets in CKD patients, and raising awareness of CKD among Primary Care Providers may improve outcomes. Socioeconomic barriers to medical care have to be identified and addressed, and patient education is a critical component of CKD care. Finally, timely start of dialysis remains a key issue.